Altitudinal body size variation in Rana kukunoris: the effects of age and growth rate on the plateau brown frog from the eastern Tibetan Plateau. Issue 2 (4th March 2022) - Yu, Tong L.; Jia, Geng; Sun, Hai Q.; Shi, Wen H.; Li, Xiao L.; Wang, Hai B.; Huang, Meng R.; Ding, Shu Y.; Chen, Jin P.; Zhang, Meng
Abstract : Body sizes in endothermic species tend to increase as temperature decreases in accordance with Bergmann's rule. However, why do some species support Bergmann's clines while others reverse it? This question should be solved by considering the relative contributions of mean age and growth rate on adult ectotherm body size. Here we studied altitudinal variation in mean body size, age, and growth rate in Rana kukunoris through 16 sites at different altitudes in the eastern Tibetan Plateau. Our results revealed that mean body size decreased as altitude increased in each sex, which fails to obey Bergmann's rule, but supports the converse Bergmann's rule. Frogs at lower altitudes tended to grow faster than individuals of the same species at higher altitudes. Conversely, age of adults did not significantly increase as altitude increased. Therefore, we suggest that lower growth rate limits the mean individual body size at the altitudes, explaining why this species follows the converse Bergmann's rule. The effect of age cannot be ignored because decreasing body length with increasing altitudes is not significant when removing the effect of age.